Multimedia computing systems and virtual reality - Tiwari Rajeev; Tiwari, Rajeev (Abingdon, Oxon ; Boca Raton, FL : CRC Press, 2022)
"This book focuses on futuristic trends and innovations in multimedia systems using big data, IoT and cloud technologies.The authors present recent advancements in multimedia systems as they relate to various application areas such as health care services and agriculture-related industries"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Multimedia systems; Virtual reality